Dynamic transformation of domain wall structure in ortho-ferrites - Shamsutdinov, M.A.; Ekomasov, E.G.; Shamsutdinov, D.M. (Functional Materials, 2004)
The stationary dynamics of domain walls in rare-earth ortho-ferrites has been studied theoretically taking into account a possibility of its structure transformation near the sound speed. The study proceeds from the fact that the total energy of the moving domain wall includes a magnetic component and a magnetostrictive one.